Viipuriin ja maailmalle : Saimaan kanavan historia - Paaskoski, Jyrki; Knapas, Rainer; Leskinen, Esa (Otava, 2002)
Resumé. - Summary. - Rezûme.
Keywords: historia; kanavaliikenne; vesirakennus; vesiliikenne; sisävesiliikenne; sisävesiväylät; laivaliikenne; vesikuljetus; kanavat (vesiväylät); Saimaan kanava; Saimaa